Skill-based Health Education for Adolescent Mental Health through the HOPE - Sri Ratna Rahayu; Lukman Fauzi; Intan Zainafree; Aufiena Nur Ayu Merzistya; Mustafa Daru Affandi; Nur Wahidah; Atika Aulia; Muhamad Zakki Saefurrohim; Zuyyinatun Muflikhah; Soesmeyka Savitri (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Globally, it is estimated that 10-20% of adolescents experience mental health problems and remains underdiagnosed and untreated. Mental health activities have not been active in Sekaran Public Health Center. Community partnership provide mental health education, training to overcome and prevent mental health problems, and to be peer educators by HOPE (Health Educated, Organized, Practiced, and Empowered) method. Twelve adolescents were screened by Strengths and Difficulties Questionnaire (SDQ). All youth cadres had normal difficulty scores, emotional symptoms, and hyperactivity. Two adolescents have threshold category in behavior problems, an adolescent has threshold category in peer problems, and an adolescent has abnormal category in proposocial behavior. There is a difference in mental health knowledge between before and after education is given (p=0,014). It is important for health facilities to regularly provide education and empowerment of adolescents in mental health. This HOPE method can be implemented for other health facilities.